Factors affecting vaccination coverage and retention of vaccination cards in Nepal. - Acharya, Kiran (2019)
ABSTRACT: This study assesses the factors associated with vaccination coverage and retention of a vaccination card among children age 12-23 months, using data from the 2016 Nepal Demographic and Health Survey. This study reveals that children born in health facilities have higher odds of vaccination coverage compared to children born elsewhere. Children who have a vaccination card are more likely to have high vaccination coverage compared to those who have never received a vaccination card. Children living in rural areas have higher odds of having a vaccination card than children in urban areas. Similarly, children living in the Hill region are more likely to have retained their vaccination card than those in the Mountain region. Children of women and men with any education are more likely to have retained their vaccination card compared with children of parents with no education. There was a significant decrease in completed vaccinations of children between 2011 and 2016. The cause is a decline in the percentage of children who received their third dose of DPT. Children whose mothers were age 35 and older had higher odds of receiving all DPT vaccinations compared to children whose mother's age was less than 20 years. Other characteristics such as having a mother who worked in the previous 12 months, having a mother who delivered her last baby in a health facility, and having a mother who retained a vaccination card are positively associated with the child receiving all DPT vaccines. KEY WORDS: vaccination, retention of vaccination card, children age 12-23 months, Nepal